2019
DOI: 10.1001/jamanetworkopen.2019.7168
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist Compliance With Therapeutic Guidelines on Diagnosis and Treatment Provision

Abstract: Key Points Question Are therapeutic guidelines effective mechanisms for ensuring compliance in the provision of over-the-counter pharmaceuticals for symptom-based requests and product-based requests in Australian pharmacies? Findings In this quality improvement study using standardized patients in scenarios of requests for emergency hormonal contraception and medication for conjunctivitis, 57.6% of pharmacies followed dispensing behavior compliant with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…However, the observation ('actual practice') showed that the information parameters have not been completely implemented. This discrepancy between work as rated (self-report) and work as done (observed) is in line with the international literature [27,29,52,[66][67][68] and has been described for developed as well as developing countries, e.g., the UK, Northern Cyprus, Indonesia and Ethiopia [27,29,52,66]. A reason for this, in addition to the feasibility of the guidelines, could be that intentions do not always translate into practice [69,70].…”
Section: The Divergence Between Perception and Practice As A Potentiasupporting
confidence: 81%
“…However, the observation ('actual practice') showed that the information parameters have not been completely implemented. This discrepancy between work as rated (self-report) and work as done (observed) is in line with the international literature [27,29,52,[66][67][68] and has been described for developed as well as developing countries, e.g., the UK, Northern Cyprus, Indonesia and Ethiopia [27,29,52,66]. A reason for this, in addition to the feasibility of the guidelines, could be that intentions do not always translate into practice [69,70].…”
Section: The Divergence Between Perception and Practice As A Potentiasupporting
confidence: 81%
“…Applying the simulated patient method (SPM), which is considered to be the “gold standard” [ 31 ] even if the relatively high administrative and financial costs and the comparably smaller sample sizes [ 31 ] as well as any intra- and inter-observer variabilities [ 32 ] are taken into account, can avoid such weaknesses because a realistic (counselling) situation can be simulated [ 33 ]. Unlike the many studies conducted in other countries [ 21 , 23 , 30 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ], in Germany, there have not been any investigations to date on the counselling and dispensing of an emergency contraceptive pill using an SPM approach because the few scientific SP studies available for Germany on the counselling quality in pharmacies are always based on indications other than emergency contraception. Clear deficits in the quality of counselling have been identified in these studies [ 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Introductionmentioning
confidence: 84%
“…To avoid a possible Hawthorne effect [ 72 ] and also a possible selection bias [ 73 ], the test purchases were carried out covertly—that is, without informing the pharmacies in advance—analogous to some other national [ 48 , 49 , 50 , 51 ] and international studies [ 21 , 33 , 38 ] and therefore pharmacies were not asked for consent to participate in advance. The lack of informed consent in advance was—analogous to the international literature [ 40 , 74 , 75 ]—resolved in that all pharmacies were informed about the procedure and the background of the study upon completion of the study. Recruited students provided their written informed consent to act as SPs.…”
Section: Methodsmentioning
confidence: 99%
“…13 BE research methods have previously been used to explore medical expert and patient communication and behaviour across a range of allied health settings, including pharmacy, reconstructive surgery and breast care nursing. 14 16 More specifically to ACP, BE research has shown that the way questions and information are framed to patients in EOL decision-making can impact their preferences and choices. 17 , 18 Studies have also explored other cognitive barriers to ACP uptake, and the potential for the use of behavioural theories in EOL care decision-making.…”
Section: Introductionmentioning
confidence: 99%